THE CHEMICAL CHARACTERISTIC OF SHRIMP WASTE-BASED SHRIMP PASTE WITH THE ADDITION OF KALAKAI LEAVES (Stenochlaena palustris) - Tyas Wara Sulistyaningrum; Ivone Christiana (Universitas Mataram, 2025)
The aim of this research was to find out the characteristics of shrimp waste-based shrimp paste with the addition of Kalakai leaves (Stenochlaena palustris) that was obtained in Palangka Raya. This research was using Completely Randomized Design (CRD) consisting of two treatments with three replications. The parameters observed were the water content test, protein content test, fat content test, and ash content test. Furthermore, the statistical test was using the ANOVA method and the BNT test with a 5% level, it showed a real difference, and with a 1% level, it showed a very real difference. It can be concluded that the chemical characteristics that was produced by shrimp paste from shrimp waste with the addition of Kalakai leaves contained 60.18% an average water content, 1.75% protein content, 0.64% fat content, 33.49% carbohydrate content, and 3.96% ash content.